The Pretended Easiness of Voice-over Translation of TV Interviews - Pilar Orero (JoSTrans: The Journal of Specialised Translation)
The article looks at the audiovisual translation mode of voice-over. Through a description of the translation process, voice-over is classified as production and postproduction, and it is the former type which is analysed here from a professional perspective. Voice-over translation for production is a complex process of translation, widely misunderstood at academic level in both fields of Film Studies and Translation Studies. It has been traditionally described as the easiest of translations in the audiovisual world, with faithfulness and synchrony as two of its main defining features. The present article analyses the many features which characterise the translation of voice-over and, in particular, the translation of live interviews.